1997
DOI: 10.1095/biolreprod56.1.194
|View full text |Cite
|
Sign up to set email alerts
|

Development of Bovine Nuclear Transfer Embryos Made with Oogonia1

Abstract: The pluripotency of embryonic germ cells in the mouse suggests that mitotic bovine fetal germ cells might also be a source of pluripotent cells. To investigate the pluripotency of bovine oogonia, the development in vitro of bovine embryos reconstructed by fusing oogonia with enucleated oocytes was compared with that of embryos made similarly with either blastomeres or granulosa cells. The donor cells (fresh oogonia, cryopreserved oogonia, 16- to 32-cell-stage blastomeres, or granulosa cells) were fused to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 43 publications
0
10
1
Order By: Relevance
“…The resulting reconstituted embryos developed to blastocyst stage with comparatively higher proportion, compared to those previously reported by others (1.8%, Moens et al. 1996; 4.3%Lavoir et al. 1997).…”
Section: Discussioncontrasting
confidence: 52%
“…The resulting reconstituted embryos developed to blastocyst stage with comparatively higher proportion, compared to those previously reported by others (1.8%, Moens et al. 1996; 4.3%Lavoir et al. 1997).…”
Section: Discussioncontrasting
confidence: 52%
“…The pluripotency of bovine gonial cells has been tested through nuclear transfer by three separate laboratories, leading to the temporary conclusion that germ cells can direct in vitro development up to blastocysts in some cases (2-4 %), but no live offspring could be obtained after transfer to recipient heifers. Only two cases of initiated pregnancy were reported [29,35] [6] which claimed that cell quiescence is a prerequisite for somatic nuclear transfer, we and others [8,51] …”
Section: Attempts With Gonial Cellsmentioning
confidence: 64%
“…It is probable, therefore, that factors specific to the NT embryos such as the transferred donor nucleus are involved in causing this high rate of binucleation. A study in bovine NT embryos (Lavoir et al, 1997) revealed a twofold higher incidence of multinucleation in embryos reconstructed with differentiated oogonia versus embryos reconstructed with blastomere nuclei. Another possible explanation is that enucleation can coincide with a high amount of actin removal, which could interfere with proper cytokinesis (Peura et al, 1998).…”
Section: Discussionmentioning
confidence: 99%